Meningkatkan Motivasi Belajar Peserta Didik Kelas XI Fase F PAKBP Materi Mengembangkan Budaya Kasih melalui Model Pembelajaran PBL SMKN 11 Malang - Y. Suwantini (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This study aims to improve the learning motivation of students in Grade XI Phase F of Catholic Religious Education and Character Education on the material of developing a culture of love by using the Problem Based Learning learning model. This study is a type of PTK research carried out in two cycles. The subjects of the study were 7 students of grade XI of SMKN 11 Malang. The data collection technique in this study used a comparative descriptive method by comparing the results from cycle 1 to cycle II. In cycle 1, the percentage of student learning motivation was 43% in the category of starting to develop and 57% in the category of developing according to expectations. While in cycle II it increased by 14% in the category of starting to develop and 86% in the category of developing according to expectations. The increase in student motivation in learning also has an impact on student learning outcomes, where in cycle 1 it obtained a percentage of 57%, while in cycle II it increased by 86%. The results of the study prove that the application of PBL also proves that students are more actively involved in learning. They become more active in group discussions, find solutions, and are involved in solving problems independently. The classroom atmosphere also became more lively, with more positive interactions between students and students with teachers. It can be concluded that by using the Problem Based Learning learning model on the material of developing a culture of love for class XI Phase F, it can help students improve their motivation and learning outcomes in the subjects of Catholic Religious Education and Character Education. In conclusion, this PBL model is effective in improving students' critical thinking skills. The recommendation is to strengthen the application of PBL, develop relevant materials, provide sufficient time for learning, and conduct regular evaluations so that learning continues to run well. With proper implementation, PBL can continue to be developed to help students develop their critical thinking skills.